International technical assistance under martial law: bureaucratic obstacles and opportunities for reform - Volkova, Yuliia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The article examines the current state of attraction and utilization of international technical assistance (hereinafter – ITA) in Ukraine under martial law conditions caused by Russia’s aggression, ongoing since 2014, and the full-scale invasion in 2022. ITA is considered a key instrument for supporting defense capabilities, economic stability, and preparation for post-war reconstruction, encompassing financial resources, military equipment, technologies, and humanitarian aid. Special attention is devoted to analyzing bureaucratic obstacles that reduce ITA effectiveness, including terminological inconsistencies between ITA and international military assistance (hereinafter – IMA), discrepancies in the regulatory framework, complexities in registration and accreditation procedures, insufficient oversight and monitoring, and limited coordination with development partners. The research methods include a dialectical approach to identify contradictions, a systemic-structural analysis of the ITA system, a comparative method to juxtapose international experiences, and an analysis of regulatory acts such as the Cabinet of Ministers of Ukraine Resolution No. 153 of February 15, 2002, «On the Creation of a Unified System for the Attraction, Use, and Monitoring of International Technical Assistance» (hereinafter – Resolution No. 153), and the Cabinet of Ministers of Ukraine Resolution No. 168 of February 13, 2024, «On Approval of the Procedure for Organizing Interaction of Central Executive Bodies and Other State Bodies Regarding the Attraction, Receipt, Transfer, Accounting, Monitoring, and Control of the Use of International Military Assistance to Meet the Needs of Security and Defense Forces During Martial Law» (hereinafter – Resolution No. 168). The findings indicate that the current ITA attraction system does not meet wartime challenges: multi-stage procedures, such as project registration with the Secretariat of the Cabinet of Ministers of Ukraine, can take weeks, critically affecting the timeliness of arms supplies. Terminological confusion between ITA and IMA significantly complicates coordination. A comprehensive reform is proposed: harmonization of the regulatory framework by integrating Resolutions No. 153 and No. 168, simplification of the registration procedure to 3–5 days, introduction of an electronic portal, development of unified control criteria, and establishment of a sectoral working group involving donors. The adaptation of international standards to Ukrainian realities is discussed, exemplified by the Paris Declaration. The results underscore the necessity of political will to implement reforms that would contribute to victory in the war and the country’s reconstruction.